2005
DOI: 10.1021/es048322g
|View full text |Cite
|
Sign up to set email alerts
|

Redox Processes and Release of Organic Matter after Thermal Treatment of a TCE-Contaminated Aquifer

Abstract: Redox conditions in heated and unheated microcosm experiments were studied to evaluate the effect of thermal remediation treatment on biogeochemical processes in subsurface environments. The results were compared to field-scale observations from thermal treatments of contaminated sites. Trichloroethene-contaminated aquifer material and groundwater from Ft. Lewis, WA were incubated for 200 days at ambient temperature (i.e., 10 degrees C) or heated to 100 degrees C for 10 days and cooled slowly over a period of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(29 citation statements)
references
References 35 publications
2
26
1
Order By: Relevance
“…Such a release of sediment-bound organic matter due to thermal treatment has been previously reported near treated source areas (Newmark andAines, 1995, Friis et al, 2005). Friis et al confirmed via experiments performed with field material that up to 8% of sedimentbound organic carbon could be released in temperature conditions usually achieved with thermal treatments (Friis et al, 2005). Releasing organic matter can be expected to affect redox conditions.…”
Section: Redox Conditionsmentioning
confidence: 95%
See 1 more Smart Citation
“…Such a release of sediment-bound organic matter due to thermal treatment has been previously reported near treated source areas (Newmark andAines, 1995, Friis et al, 2005). Friis et al confirmed via experiments performed with field material that up to 8% of sedimentbound organic carbon could be released in temperature conditions usually achieved with thermal treatments (Friis et al, 2005). Releasing organic matter can be expected to affect redox conditions.…”
Section: Redox Conditionsmentioning
confidence: 95%
“…Among the various developed remediation methods, thermal treatment by steam injection is particularly adapted for source treatment in subsurface sediments of relatively high permeability such as sandy aquifers (von Schnakenburg, 2013).This remediation strategy is known to release dissolved organic carbon (DOC) (Friis et al, 2005) the increase of which may trigger a chain of microbiallymediated redox processes. When natural attenuation has been observed prior to active source remediation, steam injection might thus influence the naturally occurring degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Sediment was transferred into diffusion-proof aluminum bags coated inside with Teflon (Friis et al 2005). Groundwater used for all microcosms was sampled at one location (B09) between 6.3 to 8.0 mbs using pre-sterilized and Ar-flushed serum bottles, as previously described (Friis et al 2006b).…”
Section: Site Description and Samplingmentioning
confidence: 99%
“…After thermal treatments are performed, elevated temperatures and unfavorable geochemical conditions (e.g., more oxic conditions), (Friis et al 2005) which have been reached during heating could limit the survival and activity of microorganisms (Friis et al 2006b). Therefore, there is a need for investigations on the sensitivity of dechlorinating microorganisms in order to establish the optimal time and conditions for bioaugmentation.…”
mentioning
confidence: 99%
See 1 more Smart Citation